Establishing an expert advisory commission to assist the G20's energy transformation processes - Andreas Löschel; Philipp Großkurth; Michel Colombier; Patrick Criqui; Du Xiangwan; Christoph Frei; Carl Friedrich Gethmann; John Gummer; Franck Lecocq; Jyoti K. Parikh; Dirk Uwe Sauer; Robert Schlögl; et al. (Kiel Institute for the World Economy (IfW), 2017)
The ongoing transformation of the world's energy systems requires an international monitoring to evaluate the transformation processes and to identify transferable leading practice policies. For this purpose, an independent scientific expert commission should be established for the G20. By actively involving political decision-makers in the discussion of the final results a broad basis of support can be ensured.
Keywords: Q01; Q48; Q58; 330; monitoring; G20; energy transformation; impact evaluation